Performance comparison of geopolymer and clay-cement grouting pastes and goaf effect evaluation of grouting backfilling method - Qin, Zhi; Shi, Quanjun; Qin, Dong; Wang, Haihua; Luo, Yuejing; Wang, Wensheng (Frontiers in Materials, 2023)
The problem of goaf treatment has become more and more prominent, posing a significant risk to the safety of transportation and causing environmental damage if it is not treated properly. This study aims to conduct a comparative analysis of various grouting pastes and evaluate their application in goaf treatment according to grouting backfilling. This research begins by discussing different grouting pastes' properties, including clay-cement composite grouting material and geopolymer grouting material, which have excellent engineering performance, environmental friendliness, and are easy to operate in complex geological environments. Moreover, the factors affecting the performance of grouting pastes, such as water-solid ratio and curing time, are also examined. Based on detailed information about the boreholes provided by drilling television, a reasonable treatment plan is formulated for goaf treatment. Finally, this study evaluates the effectiveness of different grouting pastes in real-world goaf treatment projects. The study draws the following conclusions: a direct relationship exists among flowability, setting time as well as water-solid ratio. An inverse relationship exists between the compressive strength of grouting materials and the water-solid ratio. Drilling data reveals complex goaf structures with defects such as water leakage, collapse and cavity, indicating potential geological risks in shallow areas. A treatment plan is formulated based on the geological conditions of goafs by drilling television. The effectiveness of backfill grouting in goaf areas is inspected using ground-penetrating radar (GPR) technology, and results indicate that adjusting watersolid ratio of grouting material can improve treatment effects.